Moral and Right. Conceptual contradictions in Fichte’s philosophical system of Jena’s years (1794-1799) - Scarfia, Lucas Damián (Estudios de Filosofía, 2021)
The present article states that the development of Fichte’s philosophy of Right stands in contradiction with the way that he founded the metaphysical ground of his system: morality as I’s rational and practical search to overcome the check of reality and to unify with itself. Thus, the paper exposes the impossibility to reconcile two texts: Grundlage der gesamten Wissenschaftslehre (GWL) and Grundlage des Naturrechts (GNR). In the latter, Fichte presents the Doctrine of Right and the State as mediums for the individual to reach its telos. But this affects the consistency of his thought. Although there is a hermeneutic background for this idea, it is groundbreaking as it exhibits Fichtean argumentative problems within Jena’s works. The article also takes into consideration the text: Einige Vorlesungen über die Bestimmung des Gelehrten (BG). Here Fichte incorporates several aspects from GWL and GNR that help to think on those contradictions.